2005
DOI: 10.1016/j.jacc.2005.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Aortic Stenosis in Apolipoprotein E-Deficient Mice

Abstract: Senile ApoE-deficient mice display aortic valve sclerosis that is similar to that observed in humans. The sclerotic valves displayed frequent apoptotic cell death and chemokine expression. Smooth muscle-like cells observed in degenerative valves might derive, at least in part, from bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 38 publications
4
87
0
3
Order By: Relevance
“…CAS shares some risk factors with atherosclerosis and apolipoprotein E knockout mice develop CAS (2,12,13). However, as emphasized by Otto et al (14), CAS and atherosclerosis are not synonymous, given that only half of the patients with CAS have concomitant coronary artery disease, whereas the large majority of those with atherosclerosis do not develop CAS (12).…”
Section: Alcific Aortic Stenosis (Cas)mentioning
confidence: 99%
“…CAS shares some risk factors with atherosclerosis and apolipoprotein E knockout mice develop CAS (2,12,13). However, as emphasized by Otto et al (14), CAS and atherosclerosis are not synonymous, given that only half of the patients with CAS have concomitant coronary artery disease, whereas the large majority of those with atherosclerosis do not develop CAS (12).…”
Section: Alcific Aortic Stenosis (Cas)mentioning
confidence: 99%
“…Epidemiological risk factors of AS resemble those of atherosclerosis, including elevated serum LDL cholesterol, hypertension, smoking, diabetes, and male sex (1,3,4). Furthermore, LDL cholesterol accumulates in stenotic aortic valves (5-7), and experimental AS can be induced by dietary hypercholesterolemia in animal models (8)(9)(10)(11). Finally, LDL cholesterol and its oxidation products may stimulate local inflammation in the valves and may also accelerate cell proliferation, bone matrix production, and subsequent calcification of the valves (6,9,12).…”
mentioning
confidence: 99%
“…Both CAVD lesions and atherosclerotic lesions contain inflammatory cells, with advanced lesions containing calcium deposits ). In addition, pathological studies of human stenotic valves have identified lesions similar to those in atherosclerotic plaques (Otto et al, 1994, Olsson et al, 1999, and similar lesions have been described in aortic valve leaflets of atherosclerosis in rabbits and mice (Tanaka et al, 2005, Aikawa et al, 2007b. But differences exist between the pathologies of CAVD and atherosclerosis.…”
Section: Pharmacological Treatmentmentioning
confidence: 84%
“…ApoE is a protein that allows for receptor-mediated removal of very low-density lipoprotein (VLDL) from the circulation. Spontaneous hypercholesterolemia occurs in ApoE -/-mice, and as they age, they demonstrate increased transvalvular velocity, aortic regurgitation, and nodular calcification (Tanaka et al, 2005). When subjected to a hypercholesterolemic diet, accelerated early disease is observed, characterized by thickened leaflets, activated endothelial cells, and subendothelial lesions rich in macrophages, which co-localize with MMPs, cathepsins, α-SMA, ALP, Runx2/Cbfa1, and osteocalcin expression (Aikawa et al, 2007a, Aikawa et al, 2007b.…”
Section: Murine Modelsmentioning
confidence: 99%